Multiple applications of metal-organic frameworks (MOFs) in the treatment of orthopedic diseases - Zhao, Ziwen; Wang, Chenxu; Liu, Aiguo; Bai, Ning; Jiang, Bo; Mao, Yuanfu; Ying, Ting; Dong, Daming; Yi, Chengqing; Li, Dejian (Frontiers in Bioengineering and Biotechnology, 2024)
Pharmacologic treatment of orthopedic diseases is a common challenge for clinical orthopedic surgeons, and as an important step in the stepwise treatment of orthopedic diseases, it is often difficult to achieve satisfactory results with existing pharmacologic treatments. Therefore, it is increasingly important to find new ways to effectively improve the treatment pattern of orthopedic diseases as well as to enhance the therapeutic efficacy. It has been found that metal-organic frameworks (MOFs) possess the advantages of high specific surface area, high porosity, chemical stability, tunability of structure and biocompatibility. Therefore, MOFs are expected to improve the conventional traditional treatment modality for bone diseases. This manuscript reviewed the applications of MOFs in the treatment of common clinical bone diseases and look forward to its future development.